The interrelationship between Nutrition and Periodontal Health among Children and Adults: A Literature Review - Sirma Angelova; Radostina Anastasova (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
Background and aim: Complex oral prophylaxis addressed to children and adults is conceptually related to contemporary dental medicine science and practice. Today, periodontitis is widely distributed worldwide, affecting between 40% to 90% of the global population. Many profound studies have been devoted to exploring, analyzing, and implementing the specifics of the interrelationship between dietary patterns and periodontal disorders. The purpose of the review is to investigate the interrelationship between periodontal health and nutrition among children and adults. Material and methods: An initial analysis of 229 articles was performed. We investigated all the titles, abstracts, and available full-length texts, and, based on definite criteria, these papers were elected corresponding to the interrelation between various nutrients and periodontal health in children and adults. The analyzed 61 scientific resources, including reviews, clinical reports, and research articles from PubMed, Google Scholar, NIMH, and Elsevier, have been published in the last 15 years.Results: Maintaining normal development and solid health corresponds to adequately arranged and properly performed dietary habits. Nutrition influences the health status during pregnancy and childbirth, through the stages of childhood development, and among adults. Conclusions: Scientists established that the deviations from physiologically based nutrition, such as obesity and malnutrition, can affect periodontal health throughout the life of individuals. Future investigations can be useful for the clarification of the multi-aspect interrelations between nutrition and periodontal health.